Foreign firms and local linkages: multinational affiliates and local enterprises in India - a comparative study - Ray, Pradeep Kanta; Venaik, Sunil (2001)
Few attempts have been made at addressing the question of how the degree of foreign ownership influences the propensity of firms in developing local linkages. This empirical work shows that contrary to popular belief and host-government intentions, multinational enterprise (MNE) affiliates have fewer linkages with the host-country enterprises vis-a-vis the local enterprises. Host governments need to design creative mechanisms to ensure effective alignment and achievement of both the MNE and host-country objectives. - Reproduced
Keywords: Transnational corporations